The effect of work–family conflict on emotional exhaustion and job performance among service workers: the cross-level moderating effects of organizational reward and caring. Issue 14 (6th August 2021) - Wang, I-An; Tsai, Hung-Yu; Lee, Meng-Hsiu; Ko, Ren-Chang
Abstract: This study reports on the relationships among work–family conflict (WFC), family–work conflict (FWC), emotional exhaustion and task performance of service workers. We also consider the cross-level moderating effects of organizational reward and caring on these relationships. To avoid common method variance, this study collects data from multiple levels, sources and time points. Data were collected from 238 service worker–manager pairs from 33 hotels at two different time points. The results of hierarchical linear modeling show that WFC positively relates to emotional exhaustion. In addition, organization's caring reduces the influences of WFC on emotional exhaustion. Moreover, organization's caring attenuates the negative effects of FWC on job performance. These findings have several implications for both future research and practitioners.